Marketingové plánování podniku v turbulentním tržním prostředí - Lošťáková, Hana (Univerzita Pardubice, 1998)
This paper deals with marketing planning of enterprises and its strategic business units in present changing marketing environment. The changes in a market environment require transformation of trade planning of companies into marketing planning and further require changes of content of marketing plans as a result of strategic and tactic marketing planning. This paper shows the structure of these marketing plans.
Keywords: podniky; marketingové plánování; tržní hospodářství; marketingové strategie